ANALISIS PENILAIAN KINERJA KEUANGAN PADA DANA PENSIUN UNIVERSITAS SURABAYA - Diah Anugrah Sharasanti; Ratnawati Hari Prayitno (Jurnal Bisnis Terapan, 2017)
In accordance with the Act of Pension Fund, Number 11 of 1992, the participant fee is one of the pension fund assets which should be managed in line with the investment guideline outlined by the founder and investment regulation set by the ministry. The financial performance can be assessed by comparing the finance ration and the standard ratio. In addition, it can be evaluated by comparing the finance ratio of the current year and the fiancé ratio of the previous years. This research was aimed at analyzing the financial performance of the pension fund. The subject of this research is the Pension Fund of University of Surabaya, a pension fund from the employer with fixed benefits for participants and the parties entitled. The measurement of the financial performance was conducted for the financial statement of 2011 to 2016 and it refers to the ratio of the performance evaluation of the pension fund ADPI, that is, calculating and analyzing the ratio of ROI, Operating Cost Efficiency, Investment Cost Efficiency, Fund Sufficiency Ratio, Pension fund growth ratio. The result of the study showed that the financial performance of pension fund of University of Surabaya was categorized as “good” and ranked as level one quality.